Programmable logic controllers : an emphasis on design and application - Erickson, Kelvin T. (Rolla, MO : Dogwood Valley Press, LLC, 2011)
"This book presents a comprehensive treatment of programmable logic controllers (PLCs) with an emphasis on program design. This text stresses an organized approach to developing PLC programs - "GIven a set of operational specifications, how does one develop the PLC program?" This book develops the design process: the tasks involved, breaking the program into manageable pieces, standard code for the various parts, and handling the sequential parts of the problem. Throughout, the book contains example problems demonstrating good design practice and culminated in two full-length case studies. Due to its popularity, ladder logic is employed in the majority of the text. However, the text also comprehensively covers the other four IEC 61131-3 languages: function block diagram, structured text, instruction list, and sequential function chart. These languages are covered for five PLCs: Allen-Bradley ControlLogix, Allen-Bradley PLC-5/SLC-500/MicroLogix, Modicon Unity, Siemens S7-200/300/400/1200, and GE. The main topics of this text are: PLC programming languages (with emphasis on IEC 61131-3), Structured approach to sequential problems, Good program design practice, Troubleshooting techniques, PID control, Sensors and actuators, Factory communication networks, Human-machine interface (HMI). Most chapters include student problems"--Back cover.
Introduction to PLCs -- Basic Logic Programming -- Memory Organization and Addressing -- Input/Output Modules and Installation -- Times and Counters -- Sequential Applications -- Comparison and Computation -- Other Ladder Logic Blocks -- Other Function Chart Implementations -- PID Control -- Function Block Diagram -- Structured Text -- Instruction List -- Sequential Function Chart -- Troubleshooting -- Sensors and Actuators -- Communication Networks -- Human-Machine Interface -- Control System Security -- Selecting a PLC -- Control Projects -- Example Projects -- Appendix A, Number Systems and Conversions -- Appendix B, Electrical Diagram Symbols -- Appendix C, Piping and Instrumentation Diagram (P&ID) Symbols
Errata available through web site: www.DogwoodValleyPress.com
Includes bibliographical references and index.
Keywords: Automation; Programmable controllers; Logic circuits; Programmable logic devices